2016
DOI: 10.1513/annalsats.201510-718oc
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Shortening in Middle-Aged Men with Sleep-disordered Breathing

Abstract: Intermittent hypoxemia due to obstructive sleep apnea syndrome is a major contributor to telomere shortening in middle-aged men. Oxidative stress may explain this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…In accordance with our results, Boyer and colleagues (2016) observed in a sample of middle-aged males that intermittent hypoxia, via oxygen dessaturation index, was an important contributor to telomere shortening, even controlling for confounders [18]. Similarly, Choi and colleagues found that OSA had a significant association with short telomere length, increasing the risk of brain white matter changes in a community-based cohort of aged people [20].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In accordance with our results, Boyer and colleagues (2016) observed in a sample of middle-aged males that intermittent hypoxia, via oxygen dessaturation index, was an important contributor to telomere shortening, even controlling for confounders [18]. Similarly, Choi and colleagues found that OSA had a significant association with short telomere length, increasing the risk of brain white matter changes in a community-based cohort of aged people [20].…”
Section: Discussionsupporting
confidence: 91%
“…We also found that LTL was correlated with sleep fragmentation and hypoxia-related parameters, being the last one, represented by mean SpO 2 , one of the most important predictors of LTL, after age. Although evidence from the literature had already pointed to a relationship between sleep disordered breathing and LTL [1821], the present study has described the relationship between LTL and the main pathophysiological parameters of OSAS using objective methods in a representative population sample.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…IH can also induce dyslipidaemia and insulin resistance, which develop with age. A recent study found that OSA was associated with shortened telomeres, a hallmark of ageing . In this study, the aged mice exhibited relatively high levels of collagen in the cardiac and aortic vessels, an established effect of normal ageing.…”
mentioning
confidence: 49%
“…A recent study found that OSA was associated with shortened telomeres, a hallmark of ageing. 10 In this study, the aged mice exhibited relatively high levels of collagen in the cardiac and aortic vessels, an established effect of normal ageing. In fact, the effects of IH in young mice never superseded the effects of normoxic ageing.…”
mentioning
confidence: 68%